Exploring the Relationship Between Gay Affirmative Practice and Empathy Among Mental Health Professionals. Issue 2 (April 2015) - Love, Michael M.; Smith, Adam E.; Lyall, Sarah E.; Mullins, Jaclyn L.; Cohn, Tracy J.
<x xml:space="preserve">Abstract</x> During the last several decades, psychologists have placed emphasis on multicultural competence as an essential aspect of training and practice. However, despite this emphasis, empirical data on the effects of multicultural training and practice are generally limited to variables such as race and ethnicity, with very little research on sexual minorities. However, a framework for understanding competent practice with sexual minorities does exist in the form of the concept of gay affirmative practice (GAP), which has been successfully operationalized by Crisp (2006b). Using the GAP measure and scores of empathy, the authors examined students and practitioners in the helping profession to explore the relationship between empathy and level of gay affirmative work. Findings indicated that levels of empathy predicted overall levels of GAP. The authors discuss the clinical implications of these findings and explore how the findings fit within the literature surrounding empathic understanding. Durante las últimas décadas, los psicólogos han puesto un énfasis especial en la competencia multicultural como un aspecto esencial en la formación y la práctica. Sin embargo, a pesar de este énfasis, los datos empíricos sobre los efectos de la formación multicultural y su práctica están generalmente limitados a variables como raza y etnicidad, con escasas investigaciones realizadas sobre minorías sexuales. Aun así, existe un marco teórico para comprender la práctica competente con minorías sexuales denominado terapia afirmativa gay (GAP, por sus siglas en inglés), que fue operacionalizado con éxito por Crisp (2006b). Usando las medidas GAP y puntuaciones de empatía, los autores examinaron a estudiantes y profesionales del campo de la consejería para explorar la relación entre empatía y el nivel de trabajo afirmativo con la comunidad gay. Los resultados indicaron que los niveles de empatía pronosticaron niveles totales de GAP. Los autores discuten las implicaciones clínicas de estos resultados y exploran cómo estos encajan con la literatura sobre comprensión empática.